THE PROBLEM OF THE OBJECT AND SUBJECT OF RESEARCH IN THE MODERN METHODOLOGY OF MANAGEMENT SCIENCE - Zhyvko, Zinaida; Polishchuk, Dmytro; Zarechniy, Oleksiy; Artemenko, Maryna (SWorld-Ger Conference proceedings, 2025)
The paper reveals the essence and methodological features of defining the object and subject of management science in the context of the transformation of modern scientific knowledge, and substantiates new approaches to their interpretation that meet the